Data Security Framework for Data-Centers - Kumar, Narender; Karhana, Avinash (International Journal of Computer Sciences and Engineering, 2019)
Data-centers play an important role in today's time for storing and maintaining huge amounts of data being generated daily and operated in real-time, to keep this data secure becomes as much important as keeping it stored. To address the current flaws in security policy of data-centers and to eradicate those flaws this paper suggest a new security framework for data-centers. This would provide data-centers with all kind of precautions and instructions to handle most of situations that may arise during management and other data related tasks and even after breaches by defining all data storage rules by classifying data, and defining data access rights with security policies for authentication and data verification. These all things make sure that data is secured and more reliable at both aspect storage as well as data authenticity in this framework for Data-Centers.